Estimulação transcraniana por corrente contínua associada a intervenção cognitiva em pacientes com doença de Alzheimer leve e moderada - Rodrigues, Evelyn Thais de Almeida (2021)
Alzheimer's disease (AD) is a neurodegenerative disease and the most common cause of dementia, recognized by the World Health Organization as a global public health priority. Because its pharmacological treatment does not cause a cure, supporting techniques have been studied to assist the treatment. The focus of this study was to investigate whether tDCS is able to assist in the treatment of patients with mild AD and whether the tDCS associated with cognitive intervention is effective in treating patients with moderate AD. Two articles were then developed, the first being a 2-Case Report and the second a Pilot Study. In the Case Report, cases were reported of two patients with mild AD who underwent a program of tDCS sessions over a period of 10 months, applied in six cortical regions. It has been suggested that tDCS in several regions modulates neuronal excitability, inducing long-term potentiation and changes in the synaptic receptor. In the Pilot Study, he analyzed the therapeutic effects of cognitive intervention associated tDCS in patients with moderate Alzheimer's disease. There were then 24 patients divided into two groups: active tDCS + CI and sham tDCS + CI. It was found in the second study that tDCS was able to induce an improvement in the MMSE score of these patients, but did not obtain the same result in the NPI and DAD scores. It could then be concluded that tDCS was shown to be different in patients with AD at different stages, but we must take into account that we report only 2 cases of patients with mild AD and a pilot study with patients with moderate AD.